Fusarium wilt screening technique for dry bean development - Salgado, M.; Schwartz, Howard F. (1990)
A rapid, reliable laboratory-screenhouse technique was developed to evaluate bean germplasm for resistance to and detect pathogenic variability of Fusarium oxysporum. (CIAT)